Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1080/0092623x.2013.788107
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Factors and Quality Among Mixed-Orientation Couples

Abstract: Mixed-orientation couples are defined as a heterosexual couple in which 1 partner experiences same-sex attraction and the other does not. Despite the fact that there is a sizable number of mixed-orientation couples in the U.S. adult population, few researchers have studied this population, and thus, there is limited understanding of these relationships. The authors examined the degree to which relationship commitment, partner-focused forgivingness, and marital values were associated with relationship quality, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 38 publications
(61 reference statements)
0
8
0
1
Order By: Relevance
“…For example, celibate gay Christians may reconcile a gay identity and a conservative Christian sexual ethic and faith identity but refrain from engaging in same-sex relationships (Creek, 2013;Pappas, 2013;Urquhart, 2014). Some commit themselves to celibacy, while others enter into mixed orientation marriages (Kays, Yarhouse, & Ripley, 2014), which is a marriage in which one spouse is heterosexual and the other is gay (Buxton, 2001(Buxton, , 2006Kays & Yarhouse, 2010;Kays et al, 2014). It is unclear how many gay people will pursue a mixed orientation marriage following the US Supreme Court ruling in 2015 providing for marriage equality nationwide.…”
Section: Introductionmentioning
confidence: 99%
“…For example, celibate gay Christians may reconcile a gay identity and a conservative Christian sexual ethic and faith identity but refrain from engaging in same-sex relationships (Creek, 2013;Pappas, 2013;Urquhart, 2014). Some commit themselves to celibacy, while others enter into mixed orientation marriages (Kays, Yarhouse, & Ripley, 2014), which is a marriage in which one spouse is heterosexual and the other is gay (Buxton, 2001(Buxton, , 2006Kays & Yarhouse, 2010;Kays et al, 2014). It is unclear how many gay people will pursue a mixed orientation marriage following the US Supreme Court ruling in 2015 providing for marriage equality nationwide.…”
Section: Introductionmentioning
confidence: 99%
“…When disclosure occurs, how disclosure occurs, and what partners' reactions are, likely influences the outcomes of the disclosure and relatedly, internalized stigma among pedohebephilic men. Kays et al (2014) found that 43% of the variation in mix-orientation couples' relationship quality was predicted by commitment, partner-focused forgivingness, and marital values. Relationship commitment was the single largest predictor of relationship quality, highlighting the importance of connection versus simply attraction.…”
Section: Limitations and Future Researchmentioning
confidence: 98%
“…‫لا‬ ‫دفف‬ ‫د‬ ‫د‬ ‫د‬ ‫د‬ ‫ديرجارل‬ ‫د‬ ‫د‬ ‫د‬ ‫د‬ ‫دفالدفة‬ ‫د‬ ‫د‬ ‫د‬ َ ‫ف‬ ‫ا‬ ‫د‬ ‫د‬ ‫د‬ ‫د‬ ‫د‬ ‫ايفرفف‬ ‫ي‬ ‫د‬ ‫د‬ ‫د‬ ‫د‬ ‫د‬ ‫الد‬ ‫دي‬ ‫د‬ ‫د‬ ‫د‬ ‫د‬ ‫د‬ ‫لد‬ ‫ا‬ ‫ل‬ ‫ديز‬ ‫د‬ ‫د‬ ‫د‬ ‫د‬ ‫اات‬ ‫دي‬ ‫د‬ ‫د‬ ‫د‬ ‫د‬ ‫د‬ ‫اادل‬ ‫د‬ ‫د‬ ‫د‬ ‫د‬ ‫هة‬ ‫دلاالد‬ ‫د‬ ‫د‬ ‫د‬ ‫د‬ ‫ديادلص‬ ‫د‬ ‫د‬ ‫د‬ ‫د‬ ‫ة‬ ‫ا‬ ‫ا‬ ‫لفم‬ ‫د‬ ‫لاد‬ ‫دفيا‬ ‫فا‬ ‫ا‬ ‫ديفم‬ ‫ال‬ ‫د‬ ‫دياع‬ ‫دااام‬ ‫ديرجازوث‬ ‫الدفة‬ ‫د‬ ‫داار‬ ‫فهف‬ ‫ارا‬ ‫ي‬ ‫دف‬ ‫ورة‬ (Paleari et al, 2009) ‫،ا‬ ‫دق‬ ‫د‬ ‫د‬ ‫لدال‬ ‫ا‬ ‫دي‬ ‫د‬ ‫د‬ ‫اللوف‬ ‫د‬ ‫د‬ ‫د‬ ‫داار‬ ‫د‬ ‫د‬ ‫لهم‬ ‫ار‬ ‫ي‬ ‫دف‬ ‫د‬ ‫د‬ ‫ارة‬ ‫د‬ ‫د‬ ‫د‬ ‫اع‬ ‫ده‬ ‫د‬ ‫د‬ ‫كي‬ (Lerner, 2006;Miller & Worthington, 2010;DeCaporale, 2011 (Merolla & Zhang, 2011, Merolla , Zhang & Sun, 2013Sheldon, Gilchrist-Petty & Lessley, 2014;Edwards, Pask, Whitbred & ‫ا‬ Neuendorf, 2018;Sheldon & Antony, 2018;Osei-Tutuet al, (Kachadourian, Fincham & Davila, 2004;Dinwiddie, 2008;Kays, 2010;Fincham et al, 2016…”
Section: ‫ا(‬ ‫دو‬unclassified